Integrating child rights standards in contraceptive and abortion care for minors in Africa - Kangaude, Godfrey Dalitso (Int J Gynaecol Obstet, 2022)
Minor girls in Africa face challenges in accessing high-quality contraceptive and abortion services because laws and policies are not child-friendly. Many countries maintain restrictive laws, policies, or hospital practices that make it difficult for minors to access contraception and safe abortion even when the pregnancy would risk their life or health. Further, the clinical guidelines on contraceptive and abortion care are silent, vague, or ambiguous regarding minors’ consent. African states should remedy the situation by ensuring that clinical guidelines integrate child rights principles and standards articulated in child rights treaties to enable health providers to facilitate full, unencumbered access to contraceptive and abortion care for minor girls. A sample of clinical guidelines is analyzed to demonstrate the importance of explicit, consistent, and unambiguous language about children’s consent to ensure that healthcare workers provide sexual and reproductive health care in a manner that respects child rights.